2009 Sixth International Conference on Information Technology: New Generations 2009
DOI: 10.1109/itng.2009.209
|View full text |Cite
|
Sign up to set email alerts
|

Software Testing for Web-Applications Non-Functional Requirements

Abstract: This paper tackles the use of software testing techniques for Web-Application non-functional requirements. It also shows load and performance testing application in a case study. At the end, a successful new approach for the navigability testing for WebApplications is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Load testing, as a type of non-functional testing, is a performance evaluation method used to assess how a system responds to diverse user requests. It aids in understanding how the software performs when multiple users access the system concurrently, revealing potential bottlenecks or issues related to scalability [28]. Load testing is conducted on an actual system, whether it is in the form of a prototype or a fully operational system, rather than a design on paper [29].…”
Section: Load Testingmentioning
confidence: 99%
“…Load testing, as a type of non-functional testing, is a performance evaluation method used to assess how a system responds to diverse user requests. It aids in understanding how the software performs when multiple users access the system concurrently, revealing potential bottlenecks or issues related to scalability [28]. Load testing is conducted on an actual system, whether it is in the form of a prototype or a fully operational system, rather than a design on paper [29].…”
Section: Load Testingmentioning
confidence: 99%
“…NFRs need to be validated within Agile projects through adequate testing to ensure their quality attributes have been met in the final software product. Web applications, for example, require full coverage of NFRs validation through testing [18]. This validation becomes quite clear in aA proper method for quantification of identified NFRs is necessary so they can be validated during the Agile development cycle.…”
Section: )mentioning
confidence: 99%
“…Tests can be generally divided into functional and non-functional testing. Normally non-functional tests concern the performance of the system, their usability, interoperability, portability and reliability (Hutcheson, 2003); (Naik and Tripathy, 2008); (Romano et al, 2009). Many authors have indicated the importance of performance testing and the need for appropriate methodologies for their implementation (du Plessis, 2008); (Yao et al, 2006); (Myers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such approach is organizationally difficult and very costly. Therefore, in practice, there are used special software tools for performance testing running on special testing platforms (Poston and Sexton, 1992); (Sakamoto et al, 2002); (Zhen et al, 2009); (Romano et al, 2009). These tools enable planning, load generation, execution and analysis of tests' results (Netto et al, 2011); (Myers, 2004).…”
Section: Introductionmentioning
confidence: 99%